Images from the region of the Pueblo Indians of North America - Warburg, Aby (Cornell University Press, 2016)
Aby M. Warburg (1866-1929) is recognized not only as one of the century's preeminent art and Renaissance historians but also as a founder of twentieth-century methods in iconology and cultural studies in general. Warburg's 1923 lecture, first published in German in 1988 and now available for the first time in English translation, Michael Steinberg offers offers at once a window on his career, a formative statement of his cultural history of modernity, and a document in the ethnography of the American Southwest. This edition includes thirty-nine photographs, many of them originally presented as slides with the speech, and a rich interpretive essay by the translator. Images from the Region of the Pueblo Indians of North America translates Warburg's seminal study of the "serpent ritual" of the Hopi people, which grew out of a trip to the American Southwest undertaken by Warburg in 1895-1896